Where would Ukrainian refugees go if they could go anywhere? - Mikael Elinder; Oscar Erixson; Olle Hammar (Research Institute of Industrial Economics (IFN), 2022)
We present estimates of the number of refugees expected to flee Ukraine and to which countries they are expected to migrate based on migration preferences data from the Gallup World Poll. This is important in terms of both immediate refugee assistance efforts and long-term integration policies. Our key finding is that as many as twelve million people may want to leave Ukraine permanently and that refugee policies in potential destination countries are likely to have a substantial impact on the distribution of Ukrainian refugees between different countries. More specifically, international solidarity in response to the migration crisis would significantly reduce the refugee flows to EU countries, incur a limited burden on nonEU countries, and, at the same time, better take the preferences of the Ukrainians into account.
Keywords: F22; J15; O15; 330; Ukraine; Refugees; Migration preferences